Vitamin B„ Deficiency in Macrocytic-Megalobiastic Anemia Reporting at A Tertiary Care Hospital of Sindh - Ali Akbar Shat, Fatima Qureshi, Haji Khan Khoharo , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine the frequency of vitamin B,, deficiency in macrocytic- megaloblastic anemia cases reporting at a tertiary care hospital of Sindh Methods: This cross sectional study was conducted at Isra University Hospital, Hyderabad from January 2016 to September 2017. 300 cases of macrocytic- megaloblastic anemia were selected according to criteria and vitamin 132 was estimated from the blood sera. 5 ml blood samples were centrifuged to separate sera for the vitamin B1, estimation by ELISA assay kit. Result variables were analyzed on SPSS (version 21.0) at 95% CI (P < 0.05) by Student t-test and Chi-square test for the continuous and categorical variables respectively. Results: Age was noted as 49.5±4.59 and 47.513.57 years in male and female subjects respectively (P=0.71). Of 300 subjects; male and female were noted as 153 (51%) and 147 (49%) respectively MCV in male and female was noted as 110.5±5.31 and 113.91*7.35 11 (P=0.005). Mean vitamin 13,2 level in female subjects was noted as 135.35115.51 pgiml compared to 211.6116.7 pgiml in male subjects (P41.0001). 73 (24.33%) subjects revealed normal vitamin 1312 (>240 pgitn1) levels. Remaining 227 (75.66%) subjects revealed vitamin 1312borderline, deficiency and severe deficiency levels among 119 (39.67%), 56 (18.66%) and 52 (17.33%) respectively (P=0.0001). Conclusion: The present study reports vitamin B,, deficiency of 75.66% among macrocytic-mega loblastic anemia reporting at Isra University Hospital.